Emigrants in contemporary Spanish press: A socio-cognitive approach. (June 2019) - del-Teso-Craviotto, Marisol
Abstract: This article reports on an investigation of the lemma emigra * in three mainstream Spanish newspapers from 2011 and 2015. The analysis brings together corpus-assisted Critical Discourse Analysis and Cognitive Linguistics to explore the semantic configuration of the lemma and the relationship between lexical meanings and social ideologies. Results show that in contemporary Spain, emigra * cannot simply be defined in terms of an outward population displacement, but has additional attributes derived from a shared socio-cognitive understanding of the lemma. Thus, the semantic prototype of emigra * presents emigrants as victims forced to leave their homeland because of economic reasons. Present-day Spanish emigrants, however, show additional semantic attributes that place them as peripheral members of the lexical category. Results also show that such cognitive configuration of the lemma is closely linked to different social perspectives on Spanish emigration, and provides evidence of the role media discourse has in the creation of shared socio-cognitive meanings.